Relationship Between Post Election Violence Traumatic Events and the Level of Posttraumatic Stress Disorder Among Primary school Pupils in Kibera and Kayole Settlements, Nairobi, Kenya - Mwania, Jonathan M.; Muola, James M. (International Journal of Education and Research, 2013)
This study seeks to determine whether pupils who experienced post election violence which occurred after 2007/2008 disputed elections would have higher levels of Posttraumatic Stress Disorder than those who did not. The population includes all the standard seven pupils in six primary schools in Kibera and Kayole settlements. A random sample of 164 pupils in each location has been selected. The instruments include: personal experiences during post election violence, psychological stability scale, and post traumatic experience psychological scale. The findings show that there are tremendous differences in traumatic experiences between children in the violence ridden areas and those in areas which did not witness violence and that there is a significant difference in the level of Posttraumatic Stress Disorder between pupils who experienced communal violence and those who did not. There is a high level of PTSD (75.45 percent) among the pupils who experienced violence. It is recommended that there should be a provision for parent-teacher communication; availability of school psychologists and counselors; in school setting. The establishment of school-based programs on conflict resolution, emotional literacy, and anger management skills from early childhood is also recommended.
Keywords: Violence; Trauma; Posttraumatic Stress Disorder; Psychological Stability